DNA electromagnetic properties and interactions -An investigation on intrinsic bioelectromagnetism within DNA. (3rd July 2018) - Bukhari, Masroor Hassan; Batool, Salma; Raza, Dr Yasir; Bagasra, Omar; Rizvi, Abbas; Shah, Asifa; Razzaki, Tashmeem; Sultan, Tipu
ABSTRACT: The question whether intrinsic bioelectromagnetism exists within DNA or not is an important and so far unexplored area of biology. We carried out a study of isolated genetic material, utilizing both prokaryotic and eukaryotic DNA, to measure any possible intrinsic electromagnetic effects or fields emanated within the molecules. Studies were carried out with extremely sensitive ultra-low-noise trans-impedance amplifiers and a high-precision data acquisition system to record any possible faintest electromagnetic signals from the concentrated, as well as diluted DNA, in vitro . Some experiments were performed to investigate any possible electromagnetic effects of high-frequency (HF) RF fields on the DNA under test. However, after extensive testing and careful measurements, we failed to detect any possible intrinsic or induced electromagnetic activity from the DNA as compared to simple water or empty chambers. We reached a conclusion that there does not seem to be any measurable intrinsic electromagnetic activity or fields present in the DNA material, whether in concentrated or diluted form, and if there were, any such activity or fields would be extremely minuscule to be detected with scientific precision by current human measurement methods.